COMMUNITY PRACTICE UNTUK PERFORMANCE DAN PENDAPATAN MASYARAKAT LOKAL DESA WISATA - Riski Isminar A.; Siti Nuraini; Izzato Millati; Deddy Kurniawansyah (Universitas Airlangga, 2018)
This study aims to find out the role of community practice in improving the performance of lokal communities and the income of lokal communities in Kemiren Village. This village is one of the villages targeted by the development of tourism villages by Banyuwangi Regency in line with the Ministry of Tourism program which made Banyuwangi the target of developing tourism villages. This research is a qualitative descriptive study using observation, interviews with stakeholders including village heads, BUMDes, members of the tourism conscious community with data reduction, data presentation and drawing conclusions. This study found that community practice in Kemiren Village was considered successful even though it was not maximal in improving the performance of communities around tourist villages by improving the mindset to develop to support the development of tourism villages without forgetting to preserve the environment, maintain the original culture of the village. traditional clothes for school children and civil servants on certain days, as well as contributing to increasing the income of lokal people even though the activities carried out by this community have not completely eliminated the unemployment rate or opened new jobs. This research is expected to contribute as an evaluation material that can be used by the tourism conscious community, the Village Head, other related parties to take steps to maximize existing human and natural resources, and become a reference for the development of further research